Potential health risk assessment of HFRs, PCBs, and OCPs in the Yellow River basin. (15th April 2021) - Chen, Yi-ping; Zhao, Yan; Zhao, Meng M.; Wu, Jun-Hua; Wang, Kai-bo
Abstract: The concentrations of PBDEs, NBFRs, DP, PCBs, and OCPs were analyzed in water samples of the Yellow River Basin (YRB) and in soil and maize samples collected from basin irrigation areas to understand the status of POPs and associated health risks. The results showed: (1) the congeners of eight PBDEs and seven NBFRs were detected in 10 tributaries, with average concentrations of 1575 and 4288 pg. L −1 . Thirty-three congeners of PCBs were detected, and the average concentration of PCB was 232 pg. L −1 . Five HCHs were the primary congeners among twenty-three congeners of OCPs in the ten tributaries, accounting for 79% of the total. The average concentration of OCPs was 8287 pg. L −1 . (2) Similar congeners of HFRs, PCBs, and OCPs were found in the trunk water. The ranking based on the HFR concentration was upstream > downstream > midstream, and that of the PCB and OCP concentration was downstream > upstream > midstream. (3) PCBs and OCPs in the trunk water of the YRB and in the soil and maize irrigated with river water pose potential carcinogenic and non-carcinogenic risks. The results indicate considerable organic pollution in the YRB, suggesting that national emission standards for POPs should be implemented soon. Graphical abstract: Image 1 Highlights: Ten tributaries and trunk contained POPs in the Yellow River Basin (YRB). Qin River tributaries contained special high concentration of ΣHFRs. Soil and maize irrigated with the Yellow river water also contained POPs. PCBs and OCPs pose potential carcinogenic and non-carcinogenic risks in YRB.